Phenotypic variability of retinocytomas: preregression and postregression growth patterns. Issue 6 (10th February 2012) - Abouzeid, Hana; Balmer, Aubin; Moulin, Alexandre P; Mataftsi, Asimina; Zografos, Leonidas; Munier, Francis L
Abstract : Aim: To describe the incidence of retinocytomas, their variability at presentation and their growth patterns both before and after regression. Methods: Medical notes of the 525 patients of the Jules-Gonin Eye Hospital Retinoblastoma Clinic between 1964 and 2008 were reviewed and the charts of 36 patients with retinocytomas and/or phthisis bulbi were selected. Results: The proportion of patients with retinocytomas and/or phthisis bulbi was 3.2%. The mean age at diagnosis was 28.7±17 years. Five tumours presented a cystic pattern (5.8%). Evidence of aggressive exophytic disease prior to spontaneous regression was documented in two eyes, and of invasive endophytic disease (regressed vitreous seeding or internal limiting membrane disruption) in three eyes. Twenty patients were followed with a mean follow-up of 44±60 months. Tumour growth was observed in 16% cases, benign cystic enlargement in 4% and malignant transformation in 12%. Conclusion: This large study of retinocytomas substantially expands the published features of retinocytoma by describing the cystic nature of some retinocytomas as well as clinical characteristics of the endophytic and exophytic preregression growth patterns. The authors report two different patterns of reactivation: benign cystic enlargement and malignant transformation with or without cystic growth. Higher than previously reported frequency of growth and possible life-threatening complications impose close lifetime follow-up of retinocytoma patients.